Pengaruh Perhatian Orang Tua, Fasilitas Belajar di Rumah dan Kemandirian Belajar Terhadap Prestasi Belajar Siswa SD Kelas V Se Kecamatan Parigi Barat Kabupaten Parigi Moutong - Nurfadilah; Ninik Indawati; Yuli Ifana Sari (Jurnal Penelitian dan Pendidikan IPS, 2022)
Student achievement in schools has not reached the minimum completeness criteria determined by the teacher and the school, which is 70. This problem is really realized that the acquisition of grades is influenced by various factors, be it teachers, students, learning processes and school facilities. The research objectives (1) to analyze the effect of parental attention, home study facilities and student learning independence on learning achievement, (2) to analyze the effect of parental attention on achievement, (3) to analyze the effect of home learning facilities on achievement, and (4) to analyze the effect of independent learning on achievement. The research method for the variables of parental attention, learning facilities, and independent learning is using a questionnaire. As for achievement, use report cards. The questionnaire was tested on 30 teachers using validity and reliability testing techniques. Hypothesis test using t-test for partial effect, and F-test for simultaneous effect. Data analysis used multiple linear regression formula with classical assumption test preceded. The results showed that there were significant influences, including: (1) parental attention, learning facilities, and independent learning on student achievement, (2) parental attention to student achievement, (3) learning facilities on student achievement, and (4) learning independence on student achievement.